PENINGKATAN KEMAMPUAN BERBICARA BAHASA ARAB MELALUI METODE MUHAWAROH (DIALOG) PADA SISWA KELAS VII MTs MIFTAHUL KHAIR MAKASSAR - Wahyu, Muhammad Wahyudi Syam; AP, Jufri; Kudus, Ruhul (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This research aims to enhance students' learning activities through Arabic speaking skills in the 7th grade of MTs Miftahul Khoir Makassar, utilizing the Muhawaroh (dialogue) method. This study employs a classroom action research with six 7th-grade students as the subjects. Data collection techniques include observation and tests. The research is conducted in two cycles, with each cycle consisting of two sessions. The results of the research show that the average score of students' Arabic speaking skills in Cycle I was 79, and in Cycle II it increased to 87, indicating an improvement of 8%. These findings suggest that the Muhawaroh method can be effectively applied in Arabic language learning at MTs Miftahul Khoir Makassar.